Eksistensi Transaksi Uang Digital Sebagai Alat Keuangan Modren Di Era Sekarang - Abdu Rahman Hakim; Muhammad Irwan Padli Nasution (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
In the rapid digital era, electronic money is an efficient means of life, making every transaction easier, but there are certain obstacles. The purpose of this article is that the author wants to explain the existence of e-money in e-money transactions in a comprehensive way, so that the general public can know and understand about non-cash payment instruments. This article uses a qualitative approach Library Research (Literature). The results can be seen that electronic money affects a number of companies in Indonesia such as online transportation service companies Go-jek, Grab and banking companies, these large companies use e-money in their transaction activities. BI (Bank Indonesia) itself is still promoting the use and introduction of non-cash transactions through the use of e-money. And until now BI is trying to develop and improve the system and provisions of electronic financial transactions. However, there are several aspects that affect this activity, including aspects of infrastructure availability, social and cultural aspects. In this situation, both economic actors, the community and the government must participate in implementing non-cash socialization.